Myths, Science, and Literature – Different Fields, the Same Essence - Vilma-Irén Mihály (Acta Universitatis Sapientiae: Philologica)
The present study aims at analysing the relationship and establishing the similarities between ancient Eastern myths, literature, and today’s leading scientific views such as quantum physics. In ancient times, the mythic worldview was the only one being widely accepted, a dominancy that lasted up into, roughly put, the mid-nineteenth century, when most sciences as known today started to flourish and overtook the place of mythology, invalidating it. Nowadays, however, ancient myths and modern sciences have begun getting closer to each other and, at a deep insight, one may discover that they reveal the same truth. Thus, the paper shall discuss and compare ancient Buddhist texts with leading quantum theories and literary works by Béla Hamvas and Sándor Weöres that facilitate the comprehension of the essence.